2004
DOI: 10.1088/0268-1242/19/7/002
|View full text |Cite
|
Sign up to set email alerts
|

A low-temperature and high-quality radical-assisted oxidation process utilizing a remote ultraviolet ozone source for high-performance SiGe/Si MOSFETs

Abstract: By utilizing a remote ultraviolet ozone source, a low-temperature (600-700 • C) radical-assisted oxidation (RAO) process to produce high-quality ultrathin (1.4-3.7 nm) gate oxides was successfully developed for the fabrication of high-performance SiGe/Si metal-oxide-semiconductor field effect transistors (MOSFETs). The oxide grown by this technique showed much improved leakage and breakdown properties, compared with that grown without ozone. The reactive oxygen species in the RAO process seemed to cure the unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It has been reported that the Ge-pile up at the IL/SiGe interface would increase the interface state densities. 18,19,30,31 Hence, suppressing the amounts of the Ge atoms accumulating at the IL/SiGe interface is important for the passivation of the D it . Moreover, the amounts of the Ge atoms at the IL/SiGe interface depend not only on the initial atomic fraction of Ge in the SiGe substrate, but also on the thickness of the formed IL.…”
Section: Electrical Properties Of the Il/simentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the Ge-pile up at the IL/SiGe interface would increase the interface state densities. 18,19,30,31 Hence, suppressing the amounts of the Ge atoms accumulating at the IL/SiGe interface is important for the passivation of the D it . Moreover, the amounts of the Ge atoms at the IL/SiGe interface depend not only on the initial atomic fraction of Ge in the SiGe substrate, but also on the thickness of the formed IL.…”
Section: Electrical Properties Of the Il/simentioning
confidence: 99%
“…To solve these problems, many lowtemperature oxidation processes for interlayer (IL) formation have been explored, such as O plasma 17,18 and ozone oxidation. 19,20 Although ozone oxidation is an important approach to passivate SiGe surface, the influence of the processing conditions on the interfacial and electrical properties of high-k/SiGe gate stacks has not been systematically reported, especially in thin film systems. Actually, clarifying what essentially determines the quality of the SiGe interface during the ozone oxidation processing is indispensable for us to obtain a superior high-k/SiGe interface.…”
mentioning
confidence: 99%
“…To control the interface quality, many methods have been extensively explored, such as plasma (N 2 or NH 3 ) nitridation passivation [ 4 , 5 ], sulfur passivation [ 6 ], thermal oxidation [ 7 , 8 ], low-temperature ozone passivation [ 9 , 10 , 11 , 12 ] and Si-cap passivation [ 13 ]. Among them, low-temperature ozone passivation with low thermal budge and Si-cap passivation with excellent properties of interface are considered the most promising passivation methods.…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of this method is the trade-off between the interface quality and the scalability of equivalent oxide thickness (EOT). Oxides on SiGe have also been extensively investigated as passivation layers between high-k and SiGe, which are formed by oxidizing SiGe surface via various approaches, such as thermal O 2 oxidation [9][10][11][12][13][14], O plasma [15,16], and ozone [17,18]. Conventional thermal O 2 oxidation are performed at high pressures and temperatures resulting in thick oxides and Ge-rich layers beneath the oxides, which are unsuitable as the passivation layers between high-k and SiGe.…”
Section: Introductionmentioning
confidence: 99%